Analisis Sistem Website I-Simpel Indosat Ooredoo Hutchison Sales Area Jambi berdasarkan Teori Golden Rules of User Interface Design Theo Mandel - Miftahul Jannah; Eka Rahmawati; Deva Ardhana Sapura; Albet Triadi (Departement of Mathematics Education, 2023)
One of the failures of a system is due to a user interface error that is too complicated. A complicated user interface actually makes users confused about using the system. This study aims to analyze the interface design on the I-simple website system. User interface analysis The I-simple website system uses Theo Mandel's golden rule of user interface design approach. In the golden rules of user interface design